Minding their own business : Zambia's struggle against Western control - Martin, Antony (London : Hutchinson, 1972)
Martin$1 (Bs book traces the development of Zambian economic policy up to about 1970. He shows how, under the guidance of Kenneth Kaunda, Zambia evolved from a mixed economy combining state intervention with large scale foreign investment to an economy dominated by state corporations with majority shareholdings in a large number of companies. The turning point came in August 1969, when Kaunda announced that the state was taking a 51 per cent share in the copper mines.s
lje 24/01/2018
Loans
Keywords: Economic history; Economic policy; International economic relations; Zambia